Thirty Years of Sweat Chloride Testing at One Referral Center - Faria, Alethéa Guimarães; Marson, Fernando Augusto Lima; Gomez, Carla Cristina Souza; Servidoni, Maria de Fátima; Ribeiro, Antônio Fernando; Ribeiro, José Dirceu (Frontiers in Pediatrics, 2017)
Objective To conduct a descriptive analysis of the sweat test (ST), associating ST results with epidemiological data, CFTR (cystic fibrosis transmembrane conductance regulator) mutations and reasons to indicate the ST, as well as correlating sweat sodium and sweat chloride concentrations in subjects. Methods Retrospective survey and descriptive analysis of 5,721 ST at a university referral center. Results The inclusion of the subjects was based on clinical data related with cystic fibrosis (CF) phenotype. The samples were grouped by (i) sweat chloride concentrations (mEq/L): <30: 3,249/5,277 (61.6%); ≥30 to <60: 1,326/5,277 (25.1%); ≥60: 702/5,277 (13.3%) and (ii) age: (Group A––GA) 0 to <6 months; (Group B––GB) ≥6 months to <18 years; (Group C––GC) ≥18 years. Digestive symptoms showed higher prevalence ratio for the CF diagnosis as well as association between younger age and higher values of sweat chloride, sweat sodium, and chloride/sodium ratio. The indication of ST due to respiratory symptoms was higher in GB and associated with greater age, lower values of sweat chloride, sweat sodium, and chloride/sodium ratio. There was higher prevalence of ST with sweat chloride levels <30 mEq/L in GB, ≥60 mEq/L in GC, and with borderline level in GB. There was positive correlation between sweat sodium and sweat chloride. Sweat chloride/sweat sodium and sweat sodium–sweat chloride indexes showed association with sex, reason for ST indication, and CFTR mutations. Sex alters some values presented in the ST. The number of ST/year performed before and after the newborn screening implementation was the same; however, we observed a higher number of borderlines values. A wide spectrum of CFTR mutation was found. Severe CFTR mutations and F508del/F508del genotype were associated with highest probability of ST chloride levels ≥60 mEq/L, and the absence of CFTR mutations identified was associated with borderline ST and respiratory symptoms. Conclusions ST data showed wide variability dependent on age, sex, reason for examination indication, CFTR mutations, and weight of the collected sweat sample. Sweat sodium concentration is directly correlated with sweat chloride levels and it could be used as a quality parameter.